Grade 12 students conceptual understanding of chemical reactions: a case study of flouridation - Mpofu, Nomathemba Victoria (University of the Western Cape, 2013)
Magister Educationis - MEd === The purpose of this study was to investigate grade 12 students conceptual understanding of chemical reaction using fluoridation of public water supply as a practical example of chemical reaction. The study also attempted to find out the effectiveness of concept mapping in facilitation the students understanding of chemical reaction, particularly redox reactions. === South Africa